EFFECT OF TEMPERATURE ON THE LIFE HISTORY OF Megacopta cribraria (F.) (Hemiptera: Plataspidae) REARED ON Lablab purpureus (L). (Fabaceae: Lablab) - SHAMYASREE, M. S.; JAMES, SACHIN P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
We evaluated the impact of five constant temperatures (15-35°C) on the development, survival, longevity and life table parameters of Megacopta cribraria (F.), on Lablab purpureus under laboratory conditions. The developmental time from egg to adult was negatively correlated with temperature. Temperatures between 20-30°C were ideal for development of M. cribraria. Eggs did not hatch at 15°C and the 3rd nymphal stage failed to molt to the next instar at 35°C. Female bugs exhibited highest fecundity and shortest development time at 30°C. Adult pre-oviposition period and total pre-oviposition period of females were highest at 20°C and decreased sharply at higher temperatures. Similarly, adult longevity was lowest at 30°C and highest at 20°C. The intrinsic rate of natural increase rm (0.09), finite rate of increase λ (1.09) and net reproduction rate R0 (1.87) were greatest at 30°C. These results improve our understanding of the effects of temperature on development, reproduction and population dynamics of M. cribraria, which may be used to develop improved pest management strategies.